Anti-Inflammatory Dipeptide, a Metabolite from Ambioba Secretion, Protects Cerebral Ischemia Injury by Blocking Apoptosis Via p-JNK/Bax Pathway - Zhang, Qian; Dai, Jinwei; Song, Zhibing; Guo, Yuchen; Deng, Shanshan; Yu, Yongsheng; Li, Tiejun; Zhang, Yuefan (Frontiers in Pharmacology, 2021)
MQ (l-methionyl-l-glutamic acid), anti-inflammatory dipeptide, is one of the metabolites of monocyte locomotion inhibitory factor, a thermostable pentapeptide secreted by Entamoeba histolytica. Monocyte locomotion inhibitory factor injection has been approved as an investigational drug for the potential neural protection in acute ischemic stroke. This study further investigated the neuroprotective effect of MQ in ischemic brain damage. Ischemia-reperfusion injury of the brain was induced in the rat model by middle cerebral artery occlusion. 2,3,5-triphenyltetrazolium chloride staining assay was used to measure cerebral infarction areas in rats. Laser Doppler measurement instrument was used to detect blood flow changes in the rat model. Nissl staining and NeuN staining were utilized to observe the numbers and structures of neuron cells, and the pathological changes in the brain tissues were examined by hematoxylin–eosin staining. Terminal deoxynucleotidyl transferase deoxyuridine triphosphate nick end labeling (TUNEL) staining was used to assess cell apoptosis. The changes in oxidative stress indexes, superoxide dismutase and malondialdehyde (MDA), were measured in serum. Methyl thiazolyl tetrazolium was used to measure the survival rates of PC12 cells. Flow cytometry assessed the apoptosis rates and the levels of reactive oxygen species. Real-time PCR was used to evaluate the mRNA expression levels, and Western blotting was used to analyze the changes in protein levels of p-JNK, Bax, cleaved Caspase3. We revealed that MQ improved neurobehavior, decreased cerebral infarction areas, altered blood flow volume, and the morphology of the cortex and hippocampus. On the other hand, it decreased the apoptosis of cortical neurons and the levels of MDA, and increased the levels of superoxide dismutase. In vitro studies demonstrated that MQ enhanced the cell survival rates and decreased the levels of reactive oxygen species. Compared to the oxygen-glucose deprivation/reperfusion group, the protein and mRNA expressions of p-JNK, Bax, cleaved Caspase3 was decreased significantly. These findings suggested that MQ exerts a neuroprotective effect in cerebral ischemia by blocking apoptosis via the p-JNK/Bax pathway.